Pembelajaran Energi Terbarukan Berbasis Praktikum Untuk Mengembangkan Karir Vokasional: Analisis Bibliometrik Pada Tahun 2015-2024 - Irfan, Agus; Irwanto, Irwanto; Suhendar, Suhendar; Widyaningsih, Mia (Jurnal Taman Vokasi, 2024)
This study aims to identify the development and understanding of the role of laboratory-based renewable energy education in vocational career development. This research employs bibliometric analysis using the Scopus database with the assistance of Biblioshiny and VOSviewer tools. From 2015 to 2024, 64 documents were found in Scopus and filtered down to 63 documents, comprising articles, book chapters, and conference papers relevant to the keywords "Renewable Energy Learning" OR "Practicum-Based" OR "Vocational Career Development." The data analysis over the past ten years reveals trends and the annual production of scientific articles, the most relevant sources and affiliations, the most productive countries annually, frequently used keywords, thematic maps, and the most cited documents globally. Using VOSviewer, three types of data visualizations—network, overlay, and density—support the analysis of article linkages. This study is expected to help researchers identify the development and understanding of international research related to the selected keywords and provide references and limitations for future research.